Pengaruh Label Halal, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian Obat: Study Kasus Mahasiswa Institut Agama Islam Tazkia Bogor - Ihsanul Adli; Nurizal Ismail (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of halal labels, price and service quality on drug purchasing decisions among students at the Tazkia Bogor Islamic Institute. Considering that the majority of Indonesia's population is Muslim, the halal label is an important factor in product purchasing decisions, including medicines. This research uses quantitative methods by collecting primary data through questionnaires distributed to 125 students. Data analysis was carried out using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. The research results show that the three variables, namely halal label, price, and service quality, have a significant influence on drug purchasing decisions. The halal label gives consumers confidence that the product is safe and in accordance with Islamic law, competitive prices influence consumer perceptions of product value, and good service quality increases consumer satisfaction and trust. Based on these findings, it is recommended that drug manufacturers increase halal certification, set competitive prices, and improve service quality to meet the needs and preferences of Muslim consumers, so as to increase competitiveness in the drug market